Review of beef cattle breeding research and achievements in Ethiopia - Tesfaye Alemu Tucho; Tatek Woldu; Berhanu Shelima (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
A literature review was conducted based upon 17 research reports on the beef cattle breeding activities in Ethiopia with an objective of summarizing and compiling research findings in different experiments on breeding works of beef cattle in Ethiopia and indicating future research directions. The review testifies that 27 breeds or types of cattle with 7 distinct breed categories were identified in Ethiopia. The review also summarizes the birth, weaning and yearling weights of indigenous cattle and their crosses at different levels of exotic blood. Conclusions and future research directions were also indicated in this review document.